Modelling and Analysis of Outdoor Composite Insulators Under Different Pollution Conditions - Kasmazuli, Muhammad Syafiq; Abd Rahman, Rahisham (Evolution in Electrical and Electronic Engineering, 2023)
This paper presents modelling and analysis of the electric potential and electric field of a 33kV outdoor composite insulator. While composite insulators offer benefits like hydrophobicity, lightweight, and low maintenance, they are susceptible to stress and pollutants, compromising their efficiency and leading to flashovers. The model of the insulator is developed using COMSOL Multiphysics FEA software to simulate and determine the electric potential and electric field variation across the insulator under different pollution conditions. Bird dropping, Silica sand, Salt and Dust layers were used as the variable pollution. The simulation shows the electric potential decreased by 0.452% and the electric field increased by 3.53% while in humid conditions. Meanwhile among all the polluted conditions, Silica Sand gains the highest electric potential in humid and non-humid conditions by 1.39% and 1.30% of different percentages. The highest electrical field gain in humid and non-humid was Silica Sand and Bird dropping by 83.34% and 5.03%. The graph electric potential plot shows a decrement along the insulator length. The electric field graph plots maximum values at terminal high voltage and grounding while the minimum value plots at the shed’s insulator. The increment of the polluted layer thickness increased the electric field line by 1.97% and decreased the electric potential by 0.83037%. Thus, the type of polluted conditions significantly affects the electric field and electric potential performance.